Mapping The Trends of Inclusive Education Research Based on Scopus Database: 2019-2024 - Nurjanah, Siti; Sultan, Jumriani; Martaputri, Nurul Aulia; Aisyah, Siti; Seran, D'aquinaldo Stefanus Fani (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This bibliometric analysis examines current research on inclusive education, identifying key trends, influential authors, and impactful publications. The study analyzed 1,720 articles from the Scopus database, spanning 2019 to 2024. The analysis was conducted using the VosViewer and Biblioshiny software, a web-based application included in the bibliometrics package in R. The findings reveal a consistent upward trend in publications, with Spain, the United States, Australia, the United Kingdom, and South Africa leading the research. The most cited works focus on promoting inclusion, integrating special and inclusive education, and teachers' attitudes. Thematic analysis highlights the growing emphasis on inclusive education, human factors, and technology integration. The study provides valuable insights into the multifaceted nature of inclusive education, underscoring the need for a comprehensive approach to address individual and systemic factors. As the field continues to evolve, this analysis offers a foundation for future research to enhance inclusive educational practices further and ensure equitable access to quality education for all learners.